Evaluation of 2016 MAGNIMS MRI criteria for dissemination in space in patients with a clinically isolated syndrome. (May 2018) - Hyun, Jae-Won; Huh, So-Young; Kim, Woojun; Park, Min Su; Ahn, Suk-Won; Cho, Joong-Yang; Kim, Byung-Jo; Lee, Sang-Hyun; Kim, Su-Hyun; Kim, Ho Jin
Objectives: We compared validity of 2010 McDonald and newly proposed 2016 Magnetic Resonance Imaging in Multiple Sclerosis (MAGNIMS) criteria for dissemination in space (DIS) in predicting the conversion to clinically definite multiple sclerosis (CDMS) in patients with clinically isolated syndrome (CIS). Methods: Between 2006 and 2016, we enrolled 170 patients who had a first clinical event suggestive of multiple sclerosis (MS) from seven referral hospitals in Korea. Patients were classified into two groups based on the main outcome at the last follow-up: CDMS converters, who experienced a second attack, and non-converters. Results: Of 170 patients with mean follow-up duration of 54 months, 51% converted to CDMS. The sensitivity, specificity, accuracy, and positive and negative predictive values of 2010 McDonald criteria were 70.9%, 63.1%, 67.1%, 66.3%, and 67.9%, and those for 2016 MAGNIMS criteria were 88.4%, 46.4%, 67.7%, 62.8%, and 79.6%, respectively. When we excluded 80 patients who underwent disease-modifying therapy before the second clinical event, the specificity increased to 92.3% and 84.6%, but the sensitivity decreased to 58.8% and 82.4% for 2010 McDonald and 2016 MAGNIMS criteria, respectively. Conclusion: 2016 MAGNIMS magnetic resonance imaging (MRI) criteria for DIS showed higher sensitivity but lower specificity than 2010 McDonald criteria in predicting conversion to CDMS in CIS patients.